PENERAPAN METODE PENUGASAN MANDIRI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V UPT SDN 6 RAPPANG PADA MATA PELAJARAN SBdP - Muhammad Adry Andarsumar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to improve student learning outcomes in SBdP subjects by using a social-emotional approach for class V students at UPT SDN 6 Rappang. This type of research is Classroom Action Research (PTK), using the Kemmis and McTaggart model which includes planning, action/implementation and observation, as well as reflection in each cycle. The subjects in this research were 23 students in class V UPT SDN 6 Rappang. Data collection techniques use observation, tests and documentation. Data was analyzed quantitatively and qualitatively. The indicator of success is that ≥75% of the total number of students have reached the specified KKM, namely 75. The research results show that the application of a social-emotional approach to SBdP subjects can improve the learning outcomes of class V students at UPT SDN 6 Rappang. Even though no action has been taken, the SBdP learning results for class V students at UPT SDN 6 Rappang are only 6 (29%) students who reached the KKM. In the first cycle of action activities there was an increase, namely 9 (45%) students who reached the KKM. And in cycle II as many as 19 (83%) succeeded in achieving the completion score. The average value of learning outcomes from cycle I and cycle II also increased, namely from 74 to 80.